Pengaruh Bimbingan Pengurus Pondok Terhadap Akhlakul Karimah Santri Putri di Pondok Pesantren Hidayatul Mubtadiin Jati Agung Lampung Selatan Tahun 2024/2025: Penelitian - Hariana, Difita; Habib, A.; Rahayu Ningsih, Sri (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to determine the influence of the boarding school administrators' guidance on the improvement of the female students' noble character (akhlakul karimah) at Pondok Pesantren Hidayatul Mubtadiin, Jati Agung, South Lampung. Effective guidance from the administrators is believed to play an important role in creating a conducive environment for the moral development of students, especially through guidance methods, exemplary behavior, and communication between the administrators and the students. However, there are still issues such as a lack of politeness among students and poor discipline in following the boarding school rules. This study employs a quantitative associative approach with a causal-associative research design. The sampling technique used is simple random sampling, involving 36 respondents. Data collection methods include questionnaires, observation, and documentation, which involve normality testing, linearity testing, coefficient of determination (R²), and hypothesis testing. Based on the R Square test results, the value obtained is 0.433 or 43.3%. This indicates that the independent variable, namely the guidance provided by the administrators, contributes 43.3% to the formation of the female students' noble character. Meanwhile, the remaining 56.7% is influenced by other factors not examined in this study. The results of the simple linear regression test show a significance value (sig.) of 0.003, which is smaller than the probability level of 0.05. Thus, it can be concluded that there is a significant relationship between administrators' guidance (X) and the students' noble character (Y). The t-test shows that the calculated t-value is 3.493, which is greater than the t-table value of 1.691. Therefore, the null hypothesis (Ho) is rejected, and the alternative hypothesis (Ha) is accepted. This means that there is a statistically significant influence of administrators’ guidance on the improvement of the female students’ noble character